FENOMENA GAME ONLINE DI KALANGAN MAHASISWA TEKNOLOGI PENDIDIKAN: KEBIASAAN, DAMPAK AKADEMIK, DAN POTENSI EDUKATIF - Pertiwi, Anna; Gasong, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the phenomenon of online games among Educational Technology students, focusing on playing habits, impacts on academic activities, and students' perceptions of the educational potential of online games. The research method uses a descriptive quantitative approach with a sample of 97 students (23 males and 74 females). The results showed that the majority of students play games every day (33%) with a duration of 1–2 hours/day. The type of MOBA game (Mobile Legends) is the most popular (39.2%). As many as 57.7% of students admitted that games affect study time, but 71.1% said games help reduce stress. In addition, 65% of students believe that online games have educational potential. These findings provide important implications for the development of game-based learning media and student time management.